Students’ Reading Comprehension Using Report Text For Eleventh Grade SMKN 5 Padang - Irene Beatris Semeth; Feby Meuthia Yusuf; Sherly Franchisca (Kilau Publishing, 2025)
This research was motivated by several problems in students' reading comprehension that researchers found during pre-research activities in Class XI at SMK N 5 Padang, they are lack of vocabulary, not understanding the main idea, and lack of interest in learning English. Therefore, The objective of this research was to analyze students' reading comprehension using report texts. This research used a descriptive research. researcher applied cluster random sampling to three classes, namely Class XI TPM 1, TPM 2, and TPM 3 at SMK N 5 Padang. There were 89 students as samples from three classes. The class selected from the three classes was XI TPM 1, which had 30 students. Data were obtained through multiple choice tests. The results showed that students' reading comprehension abilities were generally in the average category, with an average score of 51. As many as 0% of students were classified as very good, 13% good, 50% average, 20% poor, and 17% very poor. The most common difficulties experienced by students were in determining the main idea, understanding the meaning of words, and finding important information in the text. This shows that many students have not yet developed sufficient reading skills to understand report texts effectively.